SPIRITUALITAS CIPTAAN DAN HIDUP UGAHARI - Simanullang, Gonti (UNIKA Santo Thomas, 2003)
What is creation? Creation is all things, human beings and non human beings. What is spirituality? The Spirit is life, ruah, breath, wind. To be spiritual is to be alive, filled with ruah, breathing deeply, in touch with the wind. What, then, is creation spirituality? Creation spirituality is a way of living based on creation. In another word, we can learn a way of living by reflecting on creation itself. One of the many things we can learn from creation that makes us to be fully alive is simple living, living aerodinamically, living lightly but abundantly.